2016
DOI: 10.1080/19440049.2016.1143124
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the polycyclic aromatic hydrocarbon (PAH) content of charcoal smoke during grilling by charcoal preparation using high carbonisation and a preheating step

Abstract: Charcoal-grilling may lead to contamination of food with carcinogenic polycyclic aromatic hydrocarbons (PAHs) during the grilling process. The objective of this work was to determine the effect of charcoal preparation on 16 USEPA priority PAHs in the smoke produced during the grilling process. Firstly, mangrove charcoal was prepared at carbonisation temperatures of 500, 750 and 1000 °C. The charcoal were then preheated by burning at 650 °C. This preheating step is usually used to prepare hot charcoal for the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In addition, preheating charcoal to avoid exposure of foods to the initial wave of smoke is another effective method to prevent PAHs formation arising from smoking source. In the study by Chaemsai et al (2016), the highest PAHs concentration (19.86 µg/g) was determined in the smoke from the partially glowed charcoal which was preheated for 5 min at 500 • C, while the lowest PAHs concentration (0.15 µg/g) was in the smoke of charcoal preheated for 5 h at 1000 • C which was completely burnt. A low burning temperature for a short time resulted in the incomplete combustion of charcoal which promoted the formation of PAHs.…”
Section: 24mentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, preheating charcoal to avoid exposure of foods to the initial wave of smoke is another effective method to prevent PAHs formation arising from smoking source. In the study by Chaemsai et al (2016), the highest PAHs concentration (19.86 µg/g) was determined in the smoke from the partially glowed charcoal which was preheated for 5 min at 500 • C, while the lowest PAHs concentration (0.15 µg/g) was in the smoke of charcoal preheated for 5 h at 1000 • C which was completely burnt. A low burning temperature for a short time resulted in the incomplete combustion of charcoal which promoted the formation of PAHs.…”
Section: 24mentioning
confidence: 97%
“…A low burning temperature for a short time resulted in the incomplete combustion of charcoal which promoted the formation of PAHs. Thus, a longer preheating time for the charcoal at a higher temperature was recommended to reduce PAHs generation from smoke (Chaemsai et al., 2016).…”
Section: Factors Influencing Pahs Formation and Common Reduction Tech...mentioning
confidence: 99%
“…13 Substances contained in cigarette smoke have been well described, but the content of biomass smoke is more variable and largely depends on the type of biomass being burnt and the temperatures being used. 14 , 15 Incomplete combustion of biomass fuel produces several organic and inorganic compounds, the biological effects of which are not fully understood. Table 1 lists carcinogenic substances present in both biomass and cigarette smoke.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, modifying the drying process of olive pomace by adding a microwave pretreatment step reduced the total PAH content in the oil by 75%, which was also related to a reduction (25% to 43%) of drying time (Kiralan, Erdogdu, & Tekin, 2017). Another study found that preheating the charcoal cooker and allowing it to reach a high temperature for carbonization (approximately 750 °C) for charcoal purification before grilling the food helped to reduce PAHs in the smoke and resulted in a lower level of PAH contamination in the grilled food (Chaemsai et al., 2016). The direct deposition of PAHs from smoke produced through the incomplete combustion of thermal agents increases the PAH content in food.…”
Section: Methods To Mitigate Pahs In Foodmentioning
confidence: 99%
“…Charcoal is another efficient fuel source mainly used for smoking and grilling and has some characteristics that are superior to wood in terms of avoiding direct contact with flames and giving off practically no smoke, soot, or unburnt volatiles (Olsson & Petersson, 2003). Hot charcoal is usually prepared by preheating at 600 to 650 • C, during which may release PAHs in charcoal prior to the grilling process (Chaemsai et al, 2016). Hence, lower PAH contamination levels were observed in meat grilled with charcoal than wood (Larsson, Sahlberg, Eriksson, & Busk, 1983).…”
Section: Wood and Charcoal Typesmentioning
confidence: 99%